Hukum Tata Negara tentang Pemerintah dan Otonomi Daerah - Fitriani, Hellen Last; Nurhadi, Nurhadi (Lembaga Yasin AlSys, 2022)
State Philosophy Officially explaining the 1945 Constitution, in general, regarding the main idea in the preamble of the 1945 Constitution, it is said that